Effect of organizational communication and organizational culture on employee performance at PT. Asuransi Ramayana Jakarta - Sartika, Rawit; Astuti, Fajar Diah; Shinta, Marlina Rahmi (Journal of Economics and Business Letters, 2021)
The author's purpose in conducting this research is to determine and analyze the influence of Organizational Communication and Organizational Culture on the performance of PT. PT. Asuransi Ramayana Jakarta. This study uses the HRM theory related to employee performance, Organizational Communication, and Organizational Culture. The research uses quantitative methods with an associative approach. The sample used in this study was 55 people using a saturated sample. Data collection techniques used are interviews and questionnaires consisting of validity and reliability tests. The data analysis technique used is the Multiple Linear Regression Test, and the Classical Assumption Test consisting of normality, multicollinearity, and heteroscedasticity tests. The hypothesis consists of a t-test, f -test, and the coefficient of determination. The results of this study indicate that the variable Organizational Communication (XI) has a positive and significant effect on the performance of employees of PT. Asuransi Ramayana, Tbk Jakarta, as evidenced by the results of the t-test with t-count of 5,431 while t-table of 2,005 and having a significant number of 0.000 <0.05 Ho is rejected. The results of testing the Organizational Culture variable (X2), shows that Organizational Culture has a positive and significant effect on the performance of PT. Asuransi Ramayana, Tbk Jakarta, as evidenced by the results of the t-test with t-count of 3,473 while t=table of 2,005 and having a significant number of 0.001 <0.05 Ho is rejected, where F-count 92.868 > 3.18 F-table. Furthermore, the value of R Square in the regression model is 0.781, or 87.1% of employee performance is explained by the variables of Organizational Communication (XI) and Organizational Culture (X2) and 12.9% is explained by other factors not examined.